WONDERFULLY NATURAL - Afrion Putra Trias; Erfan Lubis; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2015)
ABSTRACT The artwork of “Wonderfully Natural” was the individual artwork that was derived from life experiences that composed in music based the ability and the influences of social and cultural environment in recent time. The aim of the mucik creation was to express the writer’s own ability in music. In this “Wonderfully Natural” artwork, the writer had tried to develop several changes on the instruments and the techniques of the music. In this wsic artwork, the writer rearrenged the initial arrangement. Moreover, the writer composed the music with combining the orginal versiion with ballada style and instrumental. The differen between these two versions was that in ballada style, it usually has the vocal or voice and in this combination, instruments was used to replace the vocal voice. Key Word : Wonderfully Natural, Beauty, Natural